Surface Free Energy Estimation: A New Methodology for Solid Surfaces. Issue 6 (24th January 2020) - Altay, Bilge Nazli; Ma, Ruoxi; Fleming, Paul D.; Joyce, Michael J.; Anand, Adarsh; Chen, Ting; Keskin, Bekir; Maddipatla, Dinesh; Turkani, Vikram S.; Kotkar, Prashant R.; Fleck, Alexander; Rasheed, Rasheed; et al.
Abstract: An interpretation of solid surfaces is generated based on physical considerations and the laws of thermodynamics. Like the widely used Owens–Wendt (OW) method, the proposed method uses liquids for characterization. Each liquid provides an absolute lower bound on the surface energy with some uncertainty from measurement variations. If multiple liquids are employed, the largest lower bound is taken as the most accurate, with uncertainty due to measurement errors. The more liquids used, the more accurate is the greatest lower bound. This method links generalizations of the Good–Girifalco equation with a general thermodynamic inequality relating the three‐interfacial tensions in a three‐phase equilibrium system. The method always satisfies this inequality with better than a 65% certainty. However, the OW seldom, if ever, conforms to this inequality and even then, the degree of satisfaction is insignificant. A reconciliation of the two methods is proposed based on rescaling the OW surface energies to conform to the inequality. This enables interpretations of dispersion and polar components of the surface energy, which are thermodynamically self‐consistent. The proposed method is also capable of dealing with material exchange between liquid and solid phases, when the surface tension and contact angle of the saturated liquids can be measured. Abstract : Directly determining the free energy of solid surfaces is an elusive endeavor. There is no direct method of measuring this energy. Proposed indirect methods are discussed in this article. Most methods start with the Young–Dupré equation: γSV = γSL + γLV cosθ. However, this is one equation in two unknowns. So at least one additional equation is necessary.